Respuesta :
Answer:
-46
Step-by-step explanation:
We need to find the common difference of this arithmetic sequence:
[tex]\frac{-26-(-10)}{10-6} =\frac{-16}{4} =-4[/tex]
So, the common difference d = -4. We can now write the equation:
[tex]a_n=a_1+d(n-1)[/tex]
[tex]a_{15}=a_6+d(15-6)=-10-4(9)=-10-36=-46[/tex]
So, the 15th term is -46.
Hope this helps!
Step-by-step explanation:
the answer and explanation is in the picture
please rate and mark as brainliest
![Ver imagen folaoye515](https://us-static.z-dn.net/files/d19/4341dd06296a6927f8174c0fce350448.jpg)